A novel built-in adjuvant metallothionein-3 aids protein antigens to induce rapid, robust, and durable immune responses - Yin, Ying; Gu, Yanfei; Zai, Xiaodong; Li, Ruihua; Zhu, Xinjie; Yu, Rui; Zhang, Jun; Wang, Shuyi; Zhang, Yue; Lin, Jian; Xu, Junjie; Chen, Wei (Frontiers in Immunology, 2022)
Adjuvants are crucial components of vaccines that can enhance and modulate antigen-specific immune responses. Herein, we reported for the first time that human metallothionein-3 (MT3), a low molecular weight cysteine-rich metal-binding protein, was a novel promising adjuvant candidate that could help protein antigens to induce rapid, effective, and durable antigen-specific immune responses. In the present study, MT3 was fused to outer membrane protein 19 (Omp19) of Brucella abortus (MT3-Omp19, MO) and C fragment heavy chain (Hc) of tetanus neurotoxin (MT3-Hc, MH), respectively. The results showed that MT3 as a built-in adjuvant increased the Omp19- or Hc-specific antibody responses by 100-1000 folds in seven days after primary immunization. Compared to other commercially available adjuvants, MT3 could stimulate earlier (4 days after primary injection) and stronger (10-100 folds) antibody response with lower antigen dose, and its adjuvanticity relied on fusion to antigen. Although the mechanism was not clear yet, the fusion protein MO was observed to directly activate DCs, promote germinal center formation and improve the speed of Ig class switching. Interestingly, our subsequent study found that other members of the mammalian MT family (human MT1 or murine MT3 for examples) also had potential adjuvant effects, but their effects were lower than human MT3. Overall, this study explored a new function of human MT3 as a novel built-in adjuvant, which may have important clinical application potential in vaccine development against global pandemics.